Rajasthan Politics and Women Empowerment (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In many low- and middle-income democracies, the entrenchment of the economic elite in politics may undermine government effectiveness by limiting the accountability of elected officials. Researchers evaluated a voter information campaign and exploited the random assignment of reservations for women in village councils to measure the impact of information and reduced incumbent advantage on village council elections. Both interventions increased the number of candidates and drove the worst performers out of the race, though in the case of the voter campaign they had short-term costs in terms of officials’ performance post-election. The effectiveness of democratic governance relies on high quality citizens entering politics and the electorate holding their representatives accountable. In many low- and middle-income democracies, the entrenchment of the economic elite in politics may undermine this process. Incumbents may be reelected despite bad performance due to voters’ lack of information. Additionally, citizens may be reluctant to seek elected office due to the costs associated with entering an election. A growing body of evidence points to the importance of entry costs in affecting candidate selection and of voter awareness for candidate selection.1 However, less is known about how voter information and entry costs influence incumbents’ decisions to re-run and for new-comers to seek office. There is also little evidence about whether reducing incumbency advantages can improve the quality of governance and government effectiveness.